Knowledge, attitudes, and practices of anaesthesia personnel towards needle stick injuries in a tertiary care hospital - Tahir, Saqiba; Hamid, Mohammad; Khan, Sobia (Journal of the Pakistan Medical Association, 2024)
The cross-sectional, prospective study was conducted at the Aga Khan University Hospital, Karachi. A questionnaire was distributed amongst anaesthesia personnel, including faculty, residents, medical officers, technicians, recovery room nurses and pain nurses working in the Department of Anaesthesiology for >3 months. Knowledge, attitudes and practices were assessed according to the operational definitions. Of the 162 respondents, 106(65.4%) were males and 56(34.6%) were females. The overall mean age was 31±6.2 years. Adequate knowledge was found in 41(25%) subjects. Overall, 56(35%) respondents reported having had a needle-stick injury, and, among them, 49(87.5%) had a positive attitude. Also, 156(96.3%) participants followed good practices. Although entirely preventable, needle stick injuries were found to be common, indicating the need for proper implementation or revision of existing policies and attainment of safe needle devices. Key Words: Health knowledge, Attitudes, Practice, Needle stick injuries, Anaesthesia.